PEMBACAAN MEMBACA TAK SEKEDAR KATA - Joko Setiyono (Ornamen, 2005)
Reading Activity is very important for human being. More over the information century today, human being is given information almost without interval. Repeat study is needed to old pattern, including reading. Reading is not only stop on verbal words to get the meaning from information which go to and from that. Because information can appear in manner of word language and aspect language. Both of them have the way of different expression. Therefore the reading will be different. Word language has the established grammatical pattern. While the aspect language has the design imagination that work with lines, area, colour, texture and also size and dimension. Taking just one of them will destroy or weaken the totality of human being absorpsion of information. Therefore the most important thing is that human being require to mater both of the languages, the language of word and aspect language.Keyword: Reading, the language